Considering COVID-19 through the Lens of Hazard and Disaster Research - Liesel Ritchie; Duane Gill (Social Sciences, 2021)
Decades of social science research have taught us much about how individuals, groups, and communities respond to disasters. The findings of this research have helped inform emergency management practices, including disaster preparedness, response, recovery, and mitigation. In the context of the COVID-19 pandemic, most of us—researchers or not—have attempted or are attempting to make sense of what is going on around us. In this article, we assert that we need not examine the pandemic in a vacuum; rather, we can draw upon scholarly and practical sources to inform our thinking about this 21st century catastrophe. The pandemic has provided an “unfortunate opportunity” to revisit what we know about disaster phenomena, including catastrophes, and to reconsider the findings of research from over the years. Drawing upon academic research, media sources, and our own observations, we focus on the U.S. and employ disaster characteristics framework of (1) etiology or origins; (2) physical damage characteristics; (3) disaster phases or cycles; (4) vulnerability; (5) community impacts; and (6) individual impacts to examine perspectives about the ways in which the ongoing pandemic is both similar and dissimilar to conceptualizations about the social dimensions of hazards and disasters. We find that the COVID-19 pandemic is not merely a disaster; rather, it is a catastrophe.